Charlie Piechart and the case of the missing pizza slice - Comstock, Eric; Sadler, Marilyn (Comstock, Eric. Charlie Piechart mystery., 2015)
When a slice of pizza goes missing Charlie sets out to find who took the missing slice, questioning each suspect in turn.